2017
DOI: 10.1177/0022034517702330
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Caries Prevention in Dental Practice

Abstract: Abstract:Background: We conducted a parallel group randomised controlled trial of children initially aged 2-3 years who were caries free, to prevent the children becoming caries active over the subsequent 36 months.Methods: The setting was 22 dental practices in Northern Ireland and children were randomly assigned by a Clinical Trials Unit (using computer generated random numbers, with allocation concealed from the dental practice until child was recruited) to the intervention (22,600 ppm fluoride varnish, too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 10 publications
2
30
0
3
Order By: Relevance
“…The findings showed that the preventive care delivered failed to prevent increment in caries experience in the studied children. The findings are in line with a newly published study from Ireland showing that biannual application of fluoride varnish did not keep children caries free during preschool age …”
Section: Discussionsupporting
confidence: 91%
“…The findings showed that the preventive care delivered failed to prevent increment in caries experience in the studied children. The findings are in line with a newly published study from Ireland showing that biannual application of fluoride varnish did not keep children caries free during preschool age …”
Section: Discussionsupporting
confidence: 91%
“…When considering caries prevention strategies, the NICPIP trial demonstrated that fluoride interventions delivered in dental practice, to children with high levels of attendance and adherence (86.7% of children attended every 6 months for 3 years in the test group and 84.5% in the control group), produce statistically significant benefits but the effect size was small and, due to the high costs of the dental workforce, of questionable cost‐effectiveness . This study suggests that, in this population, behaviour relating to restricting sugar consumption is a greater problem than promoting toothbrushing and attendant fluoride toothpaste use.…”
Section: Discussionmentioning
confidence: 85%
“…The Northern Ireland Caries Prevention in Practice (NICPIP) trial measured the effects and costs of a compound fluoride intervention delivered in dental practice which was designed to prevent caries in pre‐school children. The clinical findings of the NICPIP trial have been published elsewhere . A key finding was that, even with an 87% adherence to the preventive intervention, 34% of children developed caries.…”
Section: Introductionmentioning
confidence: 95%
“…Deshalb sollte die Durchführung der professionellen Lackapplikation routinemäßig bei den kieferorthopädischen Kontrollterminen erfolgen [24]. Hochkonzentrierte Fluoridlacke sind eine effiziente Maßnahme mit sehr guter Evidenz in der Prophylaxe der Karies [25]. Wichtig ist dabei, dass man den Lack nur an betroffenen bzw.…”
Section: Fluoridapplikation Und Zahnreinigungunclassified